The Ubiquitination System within Bacterial Host-Pathogen Interactions - Vozandychova, Vera; Stojkova, Pavla; Hercik, Kamil; Rehulka, Pavel; Stulik, Jiri (Microorganisms, 2021)
Ubiquitination of proteins, like phosphorylation and acetylation, is an important regulatory aspect influencing numerous and various cell processes, such as immune response signaling and autophagy. The study of ubiquitination has become essential to learning about host-pathogen interactions, and a better understanding of the detailed mechanisms through which pathogens affect ubiquitination processes in host cell will contribute to vaccine development and effective treatment of diseases. Pathogenic bacteria (e.g., Salmonella enterica, Legionella pneumophila and Shigella flexneri) encode many effector proteins, such as deubiquitinating enzymes (DUBs), targeting the host ubiquitin machinery and thus disrupting pertinent ubiquitin-dependent anti-bacterial response. We focus here upon the host ubiquitination system as an integral unit, its interconnection with the regulation of inflammation and autophagy, and primarily while examining pathogens manipulating the host ubiquitination system. Many bacterial effector proteins have already been described as being translocated into the host cell, where they directly regulate host defense processes. Due to their importance in pathogenic bacteria progression within the host, they are regarded as virulence factors essential for bacterial evasion. However, in some cases (e.g., Francisella tularensis) the host ubiquitination system is influenced by bacterial infection, although the responsible bacterial effectors are still unknown.